O livro didático como recurso pedagógico na educação infantil - RODRIGUES, Glenda Glycia Paz (2020)
The present work has os its theme the use of the didactic book as a pedagogical resource in early childhood education, emphasizing the history of early childhood education, the use of the book as a pedagogical resource and the autonomy of the teacher, as well as to report the experiences experienced by the teachers in Early Childhood Education in a private network school unit. It is a qualitative research in the bibliographic and field modalities, based on authors such as Piaget (1971), Ariés (1986), Vygotsky (1989), Kramer (1994), Freire (1996), Crayde and Kaercher, Alcântara (2008), Soares (2009), Oliveira (2010) and Del Priore (2013). Through the interviews these teachers expressed their opinion on the criteria used for the use of textbooks in early childhood education, the ways in which textbooks were used in early childhood education, and also answered the implications of their autonomy. It is noticed that the use of the textbook has great relevance in the classroom, especially if the teachers use it as a support for their didactic-pedagogical practices, complemented by other didactic resources in the process of teaching and learning of the students, to enable the access to other sources of knowledge without centralization in the textbook.